OXIDATIVE STRESS AND HISTOLOGICAL CHANGES INDUCED BY THE NANO-Fe2O3 IN HELIX ASPERSA - SAMIRA BENSOLTANE; MOHAMED DJEKOUN (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
everal studies show that nanoparticles (NPs) can penetrate the body through several routes and have systemic toxic effects on human health. This study aims to provide answers to the understanding of the nature and origin of the biological effects of NPs of metal oxide: Fe2O3 on a bioaccumulator and bioindicator species, the terrestrial snail Helix aspersa. Their effects were studied on snail adults by a laboratory-focused approach, and we evaluated the effect of three doses of these nanoparticles (1, 2 and 3 mg∙g-1 of food) in wheat flour for six weeks; the control group receives only flour alone. At the end of the treatment, we measured the levels of antioxidant enzymatic defences: glutathione (GSH), glutathione-S-transferase (GST), glutathione-peroxydase (GPx), malondialdehyde (MDA), catalase (CAT), and histological sections at the kidney level of each group were performed. Our results reveal triggered oxidative stress and an induction of the detoxification system, with an increase in GSH, GST, GPx and MDA levels with a decrease in catalase activity. Very clear renal tissue damage confirms the results obtained at the beginning dosages.